Programming Competitions in High School Classrooms: RITA en RED - Aybar Rosales, Vanessa del Carmen (2017)
This paper presents RITA en RED, an improvement of RITA (Robot Inventor to Teach Algorithms) that came as a results of field tests in high schools of Great La Plata. The goals of the design of RITA en RED are: to promote the introduction of block programming competitions in the classroom, providing a collaborative space for the creation and analysis of programmed robot strategies, while favoring the teaching practice through the development of proposals for teaching programming in the classroom. This paper describes experiences with RITA and the results that led to the design of RITA en RED, preliminary results of a first implementation of RITA en RED and a new design that attempts to improve the experience of the students participating in the competitions.